(untitled) (Medical Forum Monthly, 2022)
Objective: To discuss the results of supra cardiac TAPVC repair in our setup. Study Design: Retrospective study Place and Duration of Study: This study was conducted at the Pediatric Cardiac Surgery Department of Children’s Hospital Lahore for a period of 03 years from January, 2019 to November, 2021. Materials and Methods: Age, weight, presenting symptoms, operative details (like cross clamp time and cardiopulmonary bypass time), peri operative mortality, ICU stay, and complications were studied. Results: From January 2019 to November 2021, 48 patients under went repair of supra cardiac TAPVC at children’s hospital Lahore. Mean age was 13months, mean weight was 7kg, 9 (18%) patients died preoperatively. Ascending vertical vein was ligated in all cases, but in 2 patients we had to re-open the ascending vertical vein Conclusion: With only a few centers in Pakistan doing infant cardiac surgery, early outcome after repair of supra cardiac TAPVC is reasonable in our set up, but still far worse than that of modern centers. Good patient selection, and post-operative management of pulmonary hypertension can result in better outcome. In this series we did not present the follow up of the patients, which is drawback of this article.